2021
DOI: 10.1111/mbe.12283
|View full text |Cite
|
Sign up to set email alerts
|

Questions in a Life‐Sized Board Game: Comparing Caregivers' and Children's Question‐Asking across STEM Museum Exhibits

Abstract: Parkopolis, the life-sized board game, was designed to promote conversation and science, technology, engineering, and mathematics (STEM) learning. We investigated whether this exhibit also prompted questioning. Caregivers' and children's STEM-related question-asking was compared between Parkopolis (i.e., experimental group) and a STEM-themed control exhibit. Groups (N = 197) of children and caregivers visiting two exhibits in a museum were observed. Observations revealed that caregivers and children asked more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We theorize that these same "built environments, " especially in disadvantaged communities, can foster early childhood curiosity by creating interactive opportunities to engage in conversational exchanges that are dotted with questions (Gaudreau et al, 2021). Our previous research found an association between more frequent parent conversation (during share television viewing) and higher kindergarten curiosity, with a greater magnitude of association in children from low-SES families (Shah et al, 2021).…”
Section: Neighborhood Spaces As a Modifiable Ecological Context To Fo...mentioning
confidence: 98%
“…We theorize that these same "built environments, " especially in disadvantaged communities, can foster early childhood curiosity by creating interactive opportunities to engage in conversational exchanges that are dotted with questions (Gaudreau et al, 2021). Our previous research found an association between more frequent parent conversation (during share television viewing) and higher kindergarten curiosity, with a greater magnitude of association in children from low-SES families (Shah et al, 2021).…”
Section: Neighborhood Spaces As a Modifiable Ecological Context To Fo...mentioning
confidence: 98%
“…In fact, parent–child interactions during museum visits help transform children's curiosity into learning (Andre et al., 2017). While museum visits can stimulate and elicit child curiosity (Gaudreau et al., 2021; Gottfried et al., 2016), it is valuable to explore how to help visitors reap its full and wide‐ranging benefits.…”
Section: Study Bmentioning
confidence: 99%
“…Indeed, in Philadelphia, members of the community became part of the scientific team to research the impact of the installations on caregiver-child behavior and child outcomes (Hassinger-Das et al, 2020. Evaluation of PLLs in previous work reveals that PLL outcomes are measurable and align with our goals of increasing adult-child interaction quality and language use, building positive attitudes and beliefs about playful learning, 10.3389/fpsyg.2022.933320 encouraging ownership of local spaces, and increasing civic engagement (Ridge et al, 2015;Hanner et al, 2019;Bustamante et al, 2020;Hassinger-Das et al, 2020;Gaudreau et al, 2021;Shivaram et al, 2021).…”
Section: Evaluating the Modelmentioning
confidence: 99%